FRI0321 Survival rate and causes of withdrawal of belimumab treatment in sle in a real life setting. (12th June 2018) - Morello, F.; Spinelli, F.R.; Ceccarelli, F.; Massaro, L.; Novelli, L.; Miranda, F.; Perricone, C.; Truglia, S.; Alessandri, C.; Valesini, G.; Conti, F.
Abstract : Background: Systemic Lupus Erythematosus (SLE)is a chronic disease requiring long-term treatment. Even though immunosuppresive therapies improved the survival rate, a great percentage of SLE patients exhibit a persistently active disease, or disease flares. Belimumab (BLM), is currently the only biological drug approved for the treatment of active SLE patients not responding to standard of care, without active kidney or neuropsychiatric (NP)involvement. Objectives: Aim of the study was to analyse 36 months survival of BLM treatment, causes of withdrawal in a monocentric cohort of SLE patients followed-up in a daily practice setting. Methods: The study was proposed to all the patients strarting BLM. After the informed consent was obtained, demographic, clinical and serological data, indication to BLM and concomitant therapies were registered. At baseline and at 6, 12, 24, 36 months of follow-up, disease activity (SLEDAI 2K), DAS28, C3 and C4 levels, anti-dsDNA status and weekly dose of glucocorticoids were recorded. Data were expressed as median-interquartile range; after 6, 12, 24, 36 months, differences in all parameters compared to baseline were evaluated (Student t test)The treatment survival was evaluated by Kaplan-Meier analysis. P value<0.05 were considered significant. Results: We enrolled 39 Caucasian individual, 38 females, 1 male, with median age of 43 (IQR 7.5) years and median disease duration 14.5 (5.5) years. Indications for starting BLM were: mucocutaneous involvement (n=11, 28%), arthritis (n=25, 64%), systemic symptoms (n=3, 7%) and lung involvement (1 pt, 2%). At baseline, all the patients were taking PDN;97% hydroxychloroquine, 23% mycophenolate mofetil, 23% azathioprine, 5% cyclosporine, 7% methotrexate and 2% thalidomide. Table 1 summarises trend of SLEDAI 2K, C3 and C4, DAS28 (for articular involvement), prednisone dose and percentage of patients positive for anti-dsDNA during the follow-up. Fourteen out of the 39 patients (35.8%) reached 12 months of observation and only 4 the 24 months, 3 the 36 months. Figure 1 shows the survival curve of Belimumab. In 8 patients (20%) adverse events were the cause of BLM withdrawal (severe infection in one patient, severe bradychardia in one and acute infusion reaction in another one). In 4 patients (10%) BLM was discontinued for lack of efficacy(articular and skin manifestations)after 4, 8, 12 and 23 months respectively; in 6 patients (15%) for loss of efficacy; one patient developed a severe NP flare after 2nd BLM infusion and was admitted in our hospital for depression. One patient was lost during the follow-up. Two patients withdrew BLM therapy to plan a pregnancy. We found significant reduction of PDN week levels, and improvement of C4 and aDNA levels at T6; as for disease activity, we found significant reduction of DAS28 at T6, and of SLEDAI-2k at T6 and T12. Conclusions: In our monocentric cohort of SLE patients, BLM demonstrated to be effective on disease activity and serology and led to a significant decrease of glucocorticoids dose; the main causes of BLM withdrawal were adverse events or disease flares. Disclosure of Interest: None declared